Innovation Management of the Tartila Method in the School Qur'an Recitation Movement (GSM) in Lumajang Regency - Maghfiroh, Evi; Zawawi, M. Ilmil; Ni’mah, Iffatun (MANAGIERE: Journal of Islamic Educational Management, 2026)
This study analyzes the innovation, diffusion, and impact of the Tartila Method within the Gerakan Sekolah Mengaji (GSM) in Lumajang Regency. Using a descriptive qualitative case study, data were obtained from interviews, observations, and documentation involving 12 informants from JQH-NU administrators, teachers, and students. Data analysis followed Miles, Huberman, and Saldaña’s interactive model. Findings reveal that the Tartila Iqra’ Bil Qolam innovation reducing six volumes into four enhanced students’ Quranic reading and writing skills. The diffusion process aligned with Rogers’ five stages (knowledge, persuasion, decision, implementation, confirmation) and was supported by Zaltman’s facilitative, educational, persuasive, and coercive strategies. The method fostered higher student participation, parental involvement, and strengthened religious character. The study contributes to Quranic education innovation in schools and offers a model for broader application. Future studies should expand regionally and adopt mixed methods for quantitative validation.